Steroid Monotherapy for the Treatment for Pure Membranous Lupus Nephritis: A Case Series of 5 Patients and Review of the Literature - Frank Ward; Mohammad Alkhowaiter; Joanne M Bargman (Archives of Clinical Nephrology - Peertechz Publications, 2017)
Introduction: The benefi t of combination immunosuppression versus steroid monotherapy in pure membranous lupus nephritis (MLN) remains unclear. Steroid monotherapy could potentially reduce exposure to excessive immunosuppression in patients achieving remission with this strategy. The aim of this study was to defi ne patient characteristics and outcomes in MLN treated with steroid monotherapy. Method: A retrospective, observational study identifi ed all biopsy-proven pure MLN cases followed since 1990 in a single center. Demographic, clinical and histological data were gathered for patients treated with daily steroid monotherapy. The primary outcome of interest was the reduction in proteinuria, reported as  complete remission (CR), partial remission (PR) or no response. Results: We identifi ed 5 patients who received steroid monotherapy for pure MLN. The patients were 80% female with preserved renal function and little, if any, evidence of chronic interstitial fi brosis on  biopsy. The mean follow-up period was 79.4±57.6 months. All cases achieved a clinical remission (CR in two patients and PR in 3 patients). The three patients who achieved only partial remission had a relapse during follow-up, which were successfully treated by addition of further immunosuppression, whereas the two patients who achieved CR did not experience a relapse. The mean estimated GFR was similar at baseline and the latest follow-up, 117±20.7ml/min/1.73m2 vs 111±11.3ml/min/1.73m2, respectively (p=0.61). Conclusion: Daily steroid monotherapy may be an appropriate fi rst-line treatment for pure MLN. Larger, prospective, trials are needed to validate this strategy and identify those patients who are most likely to benefi t.